Implementasi Materi Kurikulum Pesantren Tentang Amaliyah Tadris dalam Mempersiapkan Santri Menjadi Guru Profesional di Pondok Pesantren Salafi dan Khalafi Banten - Nurnaesih, Nurnaesih; Wasehudin, Wasehudin; Muin, Abdul (Yayasan Rahmat Islamiyah, 2024)
The purpose of this study is to analyze in more depth the teaching, implementation, and impact of Islamic boarding school curriculum materials on amaliyah tadris activities in preparing students to become professional teachers at the Salafi and Khalafi Islamic Boarding Schools in Banten. This study uses a qualitative method with a case study approach. The data types used are primary and secondary data obtained from interviews, observations, and documentation. The data analysis technique refers to the theory of Miles Huberman, with source triangulation as a test of data validity. The results of this study show that 1). The teaching of amaliyah tadris at the Salafi Islamic Boarding School uses a hidden curriculum, while at the Khalafi Islamic Boarding School it refers to the KMI curriculum, 2) The implementation of amaliyah tadris at the Salafi Islamic Boarding School is carried out suddenly, and in uncertain conditions, while at the Khalafi Islamic Boarding School, it begins with preparing the committee, mentors, to participants and steps in implementing teaching, using Herberth's theory, and 3) The impact of amaliyah tadris at the Salafi Islamic Boarding School is the formation of a strong mentality, providing direct teaching experience, motivating students to study hard, instilling a sense of sincerity in the souls of students, and becoming a process of cadre formation for the successor to the kyai, while at the Khalafi Islamic Boarding School it is not only aimed at the formation of professional teachers, but also the formation of the souls of students in accordance with the five souls of modern Islamic boarding schools.